70 jaar Stedelijk Museum Schiedam. - Paalman, J. (Schiedam : Stedelijk Museum Schiedam)
Struycken, Peter ; Bouw, Cees ; Keizer, Jerry ; van den Broek, Jan ; Maliangkay, Evert ; Nanninga, Jaap ; Benner, Gerrit ; Corneille ; Rooskens, Anton ; Brands, Eugène ; Esser, V.P.S. ; Lichtenstein, Roy ; Ijlstra, Bouke ; Klos, Arend ; van der Vaart, Jan ; de Jong, Hans ; Wortel-van der Waerden, Anne
70 jaar Stedelijk Museum Schiedam, Stedelijk Musuem Schiedam, [1969]
boek